How the cheetahs' specialized palate accommodates its abnormally large teeth. (13th December 2016) - Steenkamp, G.; Boy, S. C.; van Staden, P. J.; Bester, M. N.
Abstract: The term focal palatine erosion was introduced into the literature to describe infection of a palatal depression palatal to the 4th maxillary premolar in cheetahs, previously hypothesized to be of pathological nature or to possibly accommodate the large mandibular molar teeth. Currently, there exists no literature that describes the normal anatomy of the palate of a cheetah ( Acinonyx jubatus ) with specific reference to these structures. The palates of six adult cheetahs, three young cheetah cubs and dry skulls of 27 cheetah, 25 lion ( Panthera leo ) and 18 leopards ( Panthera pardus ) were used in this macroscopic and microscopic study which proves the cheetah palate to have not only one but also up to three sets of palatal depressions corresponding to the cusps of the opposing mandibular cheek teeth. The largest depression caudo‐palatal to the maxillary fourth premolar tooth was always associated with a bone depression extending into the zygomatic arch bone, never described before. Through statistical analysis it is proven, for the first time, that cheetah in fact have relative macrodontia as determined by its tooth indices and comparing it to those of other African big cats namely lion and leopard. Up to eight palatal depressions are present on the palates of adult cheetahs and these are described as functional anatomical structures present to accommodate not only one but also all three opposing mandibular cheek teeth cusps. Palatal depressions are formed as the mandibular cheek teeth erupt into final occlusion and are filled up with bone and/or soft tissue after loss of the opposing mandibular teeth or its cusps, further supporting the above hypothesis. Apart from the above, the structural anatomy of the cheetah palate and vomeronasal organ was compared with that of the domestic cat. Abstract : Cheetahs have abnormally large teeth for the size of their heads compared to leopards and lions. This macroscopic and microscopic study on cheetah, lion and leopard skulls discovered that the cheetah palate has up to three sets of palatal depressions corresponding to the cusps of the opposing mandibular cheek teeth, showing how their palates are adapted to accommodate their teeth. Larger teeth, we believe, are an advantage for a predator that must consume its prey quickly.